Outcomes of early active mobilization after surgical repair of injured extensor tendon of hand and forearm - Kundu, Sujit; Dutta, Shawon; Islam, Mohammed Amirul; Alam, Daniul (International Journal of Research in Orthopaedics, 2023)
Background: Extensor tendon injuries in the hand and forearm, if left untreated, can significantly impair backhand function. Timely and effective treatment is crucial. Recent evidence suggests that early active mobilization post-surgery yields better short-term outcomes, with less disparity in long-term results. Methods: This prospective observational study was conducted at the department of orthopedic surgery, BSMMU, Dhaka, Bangladesh, from March 2014 to August 2016, with a total of 40 patients. Results: The study evaluated the efficacy of early active mobilization following surgical repair of extensor tendon injuries in zones V-VIII of the hand and forearm. At 12 weeks post-surgery, 75% of patients reported no pain, increasing to 90% at 6 months and stabilizing at 85% by 12 months. Furthermore, 75% of patients regained a range of motion greater than 120 degrees at 6 months, with 60% maintaining this at 12 months. Notably, 90% of the patients maintained normal grip strength at both 6 and 12 months. Final assessments using the Mayo wrist score showed satisfactory outcomes for 70% of patients at 12 weeks, 90% at 6 months, and 95% at 12 months. The Dargan criteria echoed these positive results, with satisfaction rates of 80% at 12 weeks, 90% at 6 months, and 95% at 12 months. Complications were minimal, including superficial skin infections (5%), hypertrophic scars (10%), and tendon rupture (5%). Conclusions: The study concludes that early active mobilization, complemented by a simple static splint, facilitates faster recovery, full range of motion, improved grip strength, and earlier return to work in the early postoperative period.